Impact of a hospital-wide hand hygiene promotion strategy on healthcare-associated infections - Ling, Moi Lin (BioMed Central, 2012)
BACKGROUND: During the Severe Acute Respiratory Syndrome (SARS) outbreak, high compliance in healthcare workers to hand hygiene was primarily driven by fear. However, the post-SARS period confirmed that this practice was not sustainable. At the Singapore General Hospital, a 1,600-bedded acute tertiary care hospital, the hand hygiene program was revised in early 2007 following Singapore's signing of the pledge to the World Health Organization (WHO) "Clean Care is Safer Care" program. FINDINGS: A multi-prong approach was used in designing the hand hygiene program. This included system change; training and education; evaluation and feedback; reminders in the workplace; and institutional safety climate. Hand hygiene compliance rate improved from 20% (in January 2007) to 61% (2010). Improvement was also seen annually in the compliance to each of the 5 moments as well as in all staff categories. Healthcare-associated MRSA infections were reduced from 0.6 (2007) to 0.3 (2010) per 1000 patient-days. CONCLUSIONS: Leadership's support of the program evidenced through visible leadership presence, messaging and release of resources is the key factor in helping to make the program a true success. The hospital was recognised as a Global Hand Hygiene Expert Centre in January 2011. The WHO multi-prong interventions work in improving compliance and reducing healthcare associated infections.